PENGARUH GAME LABIRIN TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK USIA 4-5 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN KOTA PEKANBARU - Pauziana Pauziana; Zulkifli N; Endah Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on field observations it can be seen that the ability to recornize the geometry of children aged 4-5 years has not developed optimally. So it is necessary to apply the maze game. This study aims to determine the effect of labyrinth games on the ability to recognize geometric shapes in children aged 4-5 years in Fatimah Islamic Kindergarten, Tampan District, Pekanbaru City. This study used an experimental method with one-group pretest-posttest design. The population in this study were children aged 4-5 years. The sample in this study was group A totaling 15 children. The data collection technique used is observation. The data analysis technique in this study used the t-test. The results of this research hypothesis test were obtained t = 19,000 with (Sig. 2- tailed) = 0.00 <0.05, which means that there was a significant increase after using the labyrinth game during the learning process. The influence given to the use of the labyrinthine game to the ability to recognize geometric shapes in children aged 4-5 years in the Fatimah Islamic Kindergarten in Pekanbaru is 57.57% in the medium category.Key Words: Maze Game, Ability to Know Geometry